Evolutionary Algorithms - Kristensen, Terje (Computational Intelligence, Evolutionary Computing and Evolutionary Clustering Algorithms, 2016)
The chapter describes different components of evolutionary algorithms and what is meant by mathematical optimization. In addition, genetic and evolutionary programming is defined.